2018
DOI: 10.4103/ams.ams_175_17
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional locking plate and conventional miniplates in the treatment of mandibular anterior fractures

Abstract: Context:Three-dimensional (3D) locking plates has been designed with the hypothesis that this will overcome the disadvantages of both the systems and also advantages of both systems will be combined for the management of mandibular fractures.Aims:The purpose of this study was to evaluate the efficacy of 2-mm 3D locking miniplate in the management of anterior mandibular fracture and to compare it with Champy's miniplate.Settings and Design:A prospective, randomized, clinical trial was carried out in thirty pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…On the basis of this study, we can conclude that 3D plate is an alternative approach with a similar outcome profile to miniplates. This finding was in accordance with the clinical work of Budhraja, et al: 3-D plate versus conventional miniplates (27).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the basis of this study, we can conclude that 3D plate is an alternative approach with a similar outcome profile to miniplates. This finding was in accordance with the clinical work of Budhraja, et al: 3-D plate versus conventional miniplates (27).…”
Section: Discussionsupporting
confidence: 93%
“…Farmand emphasized in his results the decrease in fixation material needed to stabilize the fracture and that no patient required additional fixation for fracture stabilization (6). The 3-D mini plates itself was a misnomer as the plates themselves were not 3 dimensional, but holds the fracture segments rigidly by resisting the 3 dimensional forces namely shearing, bending and torsional forces occurring on the fracture site in function (27).…”
Section: Discussionmentioning
confidence: 99%
“…Conflict of interest was not reported in 12 studies 12,[25][26][27]32,33,37,39,41,42,46 . In 18 studies informed consent was reported 11,13,22,23,27,29,31,[35][36][37][38][43][44][45][48][49][50][51] .…”
Section: Characteristics and Quality Of Included Primary Studiesmentioning
confidence: 99%
“…In total, 16 studies were selected for the meta-analysis. Reasons for not being included in the meta-analysis were: comparison of different diameter plates n = 5 38,39,41,44,45 (e.g., 2.0-mm locking vs. 2.3-mm non-locking), comparison of different plate designs n = 8 35,37,40,42,43,48,50,51 (i.e. 3D vs. 2.0 mm), comparison of single and double plates n = 2 36,47 , identical study n = 1 23 and duplicated study n = 1 24 .…”
Section: Meta-analysismentioning
confidence: 99%
“…Usually, two plates are used if the fractures are anterior to mental foramen and one plate for fractures posterior to foramen 5 . The Champy technique is proposed as a semi-rigid fixation 6 . The use of 3D plates for the treatment of mandibular fractures was introduced by Farmand in 1992 7 .…”
mentioning
confidence: 99%